2011
DOI: 10.1523/jneurosci.1861-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Action Potential Generation at an Axon Initial Segment-Like Process in the Axonless Retinal AII Amacrine Cell

Abstract: In axon-bearing neurons, action potentials conventionally initiate at the axon initial segment (AIS) and are important for neuron excitability and cell-to-cell communication. However in axonless neurons, spike origin has remained unclear. Here we report in the axonless spiking AII amacrine cell of the mouse retina a dendritic process sharing organizational and functional similarities with the AIS. This process was revealed through viral-mediated expression of channelrhodopsin-2-GFP (ChR2-GFP) with the AIS-targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…The presence of I Na has been verified in several later studies, as has the involvement of this current in the ability of AII amacrine cells to generate low-amplitude spikes (Boos et al, 1993;Cembrowski et al, 2012;Tamalu and Watanabe, 2007;Veruki and Hartveit, 2002a, b). Immunocytochemistry and in situ hybridization studies suggest that the channels are of the Na v 1.1 type, with an intriguing localization at a specific lobular appendage (Cembrowski et al, 2012;Kaneko and Watanabe, 2007;Wu et al, 2011), seemingly corresponding to the "morphologically distinct processes" identified in an earlier study by van Wart et al (2005). Physiological evidence for expression of voltage-gated I Ca was provided by Habermann et al (2003) and imaging experiments suggested a preferential location in the region of the cell body and lobular appendages, consistent with a role in mediating transmitter release in the chemical synapses with OFF-cone bipolar cells and ganglion cells.…”
Section: Intrinsic Conductances Of Aii Amacrine Cellsmentioning
confidence: 67%
“…The presence of I Na has been verified in several later studies, as has the involvement of this current in the ability of AII amacrine cells to generate low-amplitude spikes (Boos et al, 1993;Cembrowski et al, 2012;Tamalu and Watanabe, 2007;Veruki and Hartveit, 2002a, b). Immunocytochemistry and in situ hybridization studies suggest that the channels are of the Na v 1.1 type, with an intriguing localization at a specific lobular appendage (Cembrowski et al, 2012;Kaneko and Watanabe, 2007;Wu et al, 2011), seemingly corresponding to the "morphologically distinct processes" identified in an earlier study by van Wart et al (2005). Physiological evidence for expression of voltage-gated I Ca was provided by Habermann et al (2003) and imaging experiments suggested a preferential location in the region of the cell body and lobular appendages, consistent with a role in mediating transmitter release in the chemical synapses with OFF-cone bipolar cells and ganglion cells.…”
Section: Intrinsic Conductances Of Aii Amacrine Cellsmentioning
confidence: 67%
“…4). This lobular dendrite is likely to correspond to the process identified as displaying a cluster of voltage-gated Na + channels (Wu et al 2011; Cembrowski et al 2012) and having a characteristic ultrastructure in electron microscopic investigations (Tsukamoto and Omi 2013). It is also possible to observe that lobular dendrites can extend into the inner nuclear layer (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Despite morphological variability, these cells display a set of common characteristics that together contribute to defining them as a cell type. AII amacrine cells have been characterized as axon-less, narrow-field, bistratified retinal interneurons and their general morphological characteristics have been identified in a variety of different mammalian species at the light microscopic level, including cat (Kolb and Famiglietti 1974; Famiglietti and Kolb 1975; Kolb et al 1981; Vaney 1985), dog (Cajal 1892; Famiglietti and Kolb 1975), mouse (Wu et al 2011; Cembrowski et al 2012), primate (Polyak 1941; Boycott and Dowling 1969; Famiglietti and Kolb 1975; Kolb et al 1992; Wässle et al 1995), rabbit (Dacheux and Raviola 1986; Mills and Massey 1991; Vaney et al 1991), and rat (Perry and Walker 1980; Boos et al 1993; Wässle et al 1993; Mørkve et al 2002). The number of studies of AII amacrine cells at the electron microscopic level is smaller, but includes cat (Kolb and Famiglietti 1974; Famiglietti and Kolb 1975; Kolb 1979), mouse (Tsukamoto and Omi 2013), primate (Wässle et al 1995), rabbit (Dacheux and Raviola 1986; Strettoi et al 1992; Marc et al 2014), and rat (Chun et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Light flashes evoked depolarizing responses during the current clamp segment of the protocol as shown in Figure 8B. Note that small action potentials (spikelets) are present in the AII-AC light response and these are likely generated by the axon-initial-segment-like process of AII-AC (Wu et al, 2011; Cembrowski et al, 2012). As shown in Figure 8C, the light stimuli produced ΔC m jumps that were correlated with light intensity.…”
Section: Resultsmentioning
confidence: 99%